DIFFUSE CARCINOMAS OF THE BREAST: CLINICAL AND MORPHOLOGICAL PROFILING BASED ON QUPATH/IMAGEJ - Yigitaliyev Alisher Bakhodir ugli; Tursunov Khasan Ziyayevich; Gafur-Okhunov Mirza-Ali Aliyarovich; Akhrayeva Dilnoza Bakhtiyarovna (Scholar Express Journals, 2025)
In the study, the clinical and morphological features of diffuse breast carcinomas (ductal, lobular, and inflammatory variants) were assessed using digital morphometry. Biopsy materials were scanned in the NanoZoomer system and analyzed using the QuPath and ImageJ programs. Stroma, lobules, blood vessels, and the nuclear-cytoplasmic index (NCI) were measured as the main indicators.
Keywords: Breast Cancer; Diffuse Forms; Ductal Invasive Carcinoma